Vortex-assisted low density solvent and surfactant based dispersive liquid–liquid microextraction for sensitive spectrophotometric determination of cobalt. Issue 13 (14th February 2018) - Chaiyamate, Patiwat; Seebunrueng, Ketsarin; Srijaranai, Supalax
Abstract : The formation of a Co(II)–PV complex and the VALS-DLLME procedure. Abstract : This study describes the development of vortex-assisted low density solvent and surfactant based dispersive liquid–liquid microextraction (VALS-DLLME) for Co(ii ) prior to its spectrophotometric detection. The method consisted of the complexation of Co(ii ) with pyrocatechol violet (PV) followed by the preconcentration of the Co(II)–PV complex using VALS-DLLME and then an absorption measurement at 600 nm. The optimum conditions for complex formation were a 1 : 3 mole ratio of Co(ii ) and PV at pH 7.5, while the conditions for VALS-DLLME were 300 μL 1-dodecanol as extraction solvent, and 300 μL acetonitrile as dispersive solvent under a vortex for 20 s with the addition of cationic surfactant (0.02 mmol L −1 CTAB). Under the optimum conditions, good linearity was in the range of 0.1–10 mg L −1, the enrichment factor (EF) was 13.5 and the low limit of detection (LOD) was 0.04 mg L −1 . The method was applied to the analysis of Co(ii ) in water, green leaf vegetable and vitamin B12 samples. The proposed method provided good recoveries in the range of 86–104%, which were comparable to those obtained from flame atomic absorption spectrophotometry.